Sleep hygiene mediates the association between sleep quality and symptoms of fatigue, anxiety and depression in prostate cancer patients - Kathleen T. Galvin; Sheila N. Garland; Shaun Costello; Andre Aumata; Ramakrishnan Mani; Erik Wibowo (Cancer Survivorship Research & Care)
Introduction Prostate cancer (PCa) treatment impairs sleep and psychological well-being. We aim to determine if sleep hygiene mediates the relationship between sleep quality, fatigue, anxiety and depression in PCa patients.Methods Fifty-one participants completed questionnaires on sleep, sleep hygiene and psychological well-being, and one-week sleep-wake measurement using actigraphy.Results Over 25% of participants frequently got out of bed at inconsistent times, used alcohol/tobacco/caffeine close to bed time, and used bed for activities other than sleeping or sex. Close to 40% frequently engaged in multiple poor sleep hygiene. Feeling stressed, angry, upset, or nervous while in bed partially mediated the relationships between insomnia symptoms and anxiety or depressive symptoms, and fully mediated the associations between: (1) wake after sleep onset (WASO) and fatigue symptoms, (2) insomnia symptoms and fatigue symptoms, and (3) WASO and depressive symptoms. Thinking, planning, or worrying while in bed partially mediated the relationships between number of awakening or insomnia symptoms and anxiety symptoms, and fully mediated the association between WASO and fatigue symptoms. Taking long daytime naps partially mediated the relationship between sleepiness and fatigue symptoms.Conclusion Sleep hygiene education may help PCa patients avoid behaviors that worsen their sleep and psychological well-being.